2020
DOI: 10.1039/c9ra08823g
|View full text |Cite
|
Sign up to set email alerts
|

Optimized performance III-nitride-perovskite-based heterojunction photodetector via asymmetric electrode configuration

Abstract: Enhanced perovskite/GaN-based broad-band photodetector is demonstrated by optimizing electrode configurations. The detection capability of the optimized perovskite/GaN structure was extended to UV range with fast response and high responsivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…28, 29 and comparable with ref. 27 Significantly longer fall time observed for 405 nm illumination may be ascribed to anomalous-like transient photocurrent behavior detected at below-GaN illumination regime. Such a shape of photocurrent has been already observed for organic part-containing semiconductors.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…28, 29 and comparable with ref. 27 Significantly longer fall time observed for 405 nm illumination may be ascribed to anomalous-like transient photocurrent behavior detected at below-GaN illumination regime. Such a shape of photocurrent has been already observed for organic part-containing semiconductors.…”
Section: Resultsmentioning
confidence: 93%
“…6(c) and (d), respectively. The rise time ( t on – counted from 10% to 90% of the maximum current) and fall time ( t off – from 90% to 10% of the maximum current) 27 are calculated for each illumination wavelength and depicted in the figures. Obtained rise times are 72 ms and 63 ms, while fall times are 62 ms and 110 ms for 325 nm and 405 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…5 Mitra et al reported on a heterojunction structure of a CH 3 NPbI 3 MAPI/p-type GaN PD, which displayed a broadband spectrum by introducing wide-band-gap semiconductors. 11 A high-stability self-powered perovskite photodetector based on a CH 3 NH 3 PbI 3 /GaN heterojunction was fabricated, expanding the response wavelength of a perovskite PD to the UV region owing to the wide band gap of GaN. 32 In this work, we report on a BA 2 PbI 4 /GaN heterojunction PD, which exhibits a broadband photoresponse from the UV to visible range and is capable of good rectifying behavior in dark conditions.…”
Section: Introductionmentioning
confidence: 97%
“…8−10 Recently, OIPs have shown great application potential in broadband photoresponse detection. 11,12 However, stability issues in the OIP materials, particularly in the 3D structure, can block their applications in the development of devices. 13−15 In order to reduce the adverse effect of instability on the device performance, it has been shown that reducing the dimensionality can improve material stability as well as creating new functionalities in these materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation